PELATIHAN PEMBUATAN KARYA SENI RUPA MELALUI TEKNIK KOLASE, MONTASE DAN MOZAIK PADA GURUDI SDN 67 KOTA BENGKULU - Dwi Anggraini; Hasnawati -; Pebrian Tarmizi (Universitas Bengkulu, 2018)
This training is motivated by the needs of the 2013 curriculum for thematic teaching practices which contain subjects of SBDP in the field of fine arts at primary school level. This activity aims to improve the competence of classroom teachers both theoretically and practically in makingof artwork using collage, montage and mosaic techniques. The method used is training and mentoring. Data collection techniques are observations to describe the process of collage, montage, and mosaic works and the implementation of collage, montage and mosaic learning in the classroom and tests to measure teacher knowledge (pretest and posttest). The results of this activity show that teachers can follow the process of training and practice, and the results of pretest and post-test show an increase only 17.65% of teachers who can get value of ? 60 during the pretest, then increase to 73.53% of teachers are able to get value of ? 60 at post-test. The conclusion is this activity can increase the knowledge of the target teacher in terms of both theoretical and practice.Keywords: artwork, collage, mosaic, montage